2019
DOI: 10.1002/mus.26499
|View full text |Cite
|
Sign up to set email alerts
|

Nerve conduction normal values for electrodiagnosis in pediatric patients

Abstract: Introduction Existing normal value references for pediatric nerve conduction studies (NCS) are based on limited sample sizes with uncertain reliability, suggesting a need for better normative data. Methods Electronic medical records were reviewed for pediatric patients (0 to <18 years) with normal findings on electromyography and NCS during the period from January 1, 1997 through September 20, 2017. Electrodiagnostic and demographic data were collected. Gaussian and descriptive statistics were used to establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
57
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 22 publications
11
57
3
Order By: Relevance
“…The AANEM's Normative Data Taskforce established criteria for evaluating articles under consideration as normative standards . Applying those criteria to published pediatric studies yielded seven articles published in peer‐reviewed journals since 1980 that provide high‐quality normative data, from preterm infants to older children (Table ). One additional article with a cohort of 92 children was included as it approached the 100‐patient threshold established by the AANEM task force (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AANEM's Normative Data Taskforce established criteria for evaluating articles under consideration as normative standards . Applying those criteria to published pediatric studies yielded seven articles published in peer‐reviewed journals since 1980 that provide high‐quality normative data, from preterm infants to older children (Table ). One additional article with a cohort of 92 children was included as it approached the 100‐patient threshold established by the AANEM task force (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The most recent study, with by far the largest cohort, is Ryan et al, which includes data from a large set of 1,918 NCSs performed on 1,849 unique pediatric patients, stratified into multiple age groups. Lower limits for amplitude and conduction velocity, and upper limits for distal latency, were provided for values at the 5th percentile or 95th percentile, respectively (ie, 2 SD below or above the mean).…”
Section: Resultsmentioning
confidence: 99%
“…After excluding duplicate studies and studies in a foreign language from the aforementioned relevant publications, a total of 39 relevant studies were used for this comprehensive review. 21 studies used electrophysiological techniques for NBPP diagnosis and prognosis in clinical scenarios [9,17,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Three articles utilized animal models for reporting electrophysiological parameters of avulsed or stretched BP [45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…In the first three years of life, the ulnar nerve conduction velocity increased rapidly, while the median nerve conduction velocity slowly increased in the first year of life with a rapid increase in the adolescent years [27]. [27,28,30,33,35,41]. , latency to the start of the potential from stimulus artifact (L1), and latency to peak potential (L2) and B) H-reflex, a late response measure when the stimulus directly stimulates the motor nerve fibers (adapted from [40]).…”
Section: Human Nerve Conduction Studies In Normal Uninjured Brachiamentioning
confidence: 99%
“…Upon the initial encounter, nerve conduction studies were performed, as described previously (Table 1). 3 They showed no response from the right sural sensory and fibular motor nerves. The right median, ulnar, and tibial motor nerve conduction studies showed prolonged distal latencies, slowed velocities, and low to normal amplitudes.…”
Section: On Initial Examination Strength Was 4/5 On the Medical Resementioning
confidence: 95%